Characterization of a Novel Methyl-Accepting Chemotaxis Gene, dmcB, from the Oral Spirochete Treponema denticola - Li, Hong (American Society for Microbiology, 1999)
Immediately downstream from the previously isolated Treponema denticola ATCC 35405 prtB gene coding for a chymotrypsinlike protease activity, an open reading frame, ORF3, was identified which shared significant homology with the highly conserved domains (HCDs) of bacterial methyl-accepting chemotaxis proteins (MCPs). Nucleotide sequencing of this ORF revealed that the gene would code for a protein with a size of approximately 41 kDa. In addition, this sequence contained a domain which was virtually identical to the HCD of a recently characterized MCP, DmcA, of strain 35405. Therefore, this ORF was named dmcB. Northern blot analysis suggested that dmcB was part of an operon structure containing prtB. Insertional inactivation of dmcB utilizing an ermF-ermAM cassette resulted in a mutant with decreased chemoattraction toward nutrient supplements. In addition, the mutant displayed an altered pattern of methylated proteins under conditions of chemotaxis. Inactivation of the dmcB gene also attenuated the methylation of the DmcA protein. These results suggest that the dmcB gene codes for an MCP in T. denticola which may interact with other MCPs in these organisms.